Vacation under the volcano - Osborne, Mary Pope (Osborne, Mary Pope. Magic tree house series, 1998)
Their magic tree house takes Annie and Jack to Pompeii just as Vesuvius is about to erupt, and they must find a Roman scroll before everything is covered with burning ash.